2017
DOI: 10.9734/arrb/2017/32509
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Organic, Inorganic and Biofertilizers on Soil Microbial Activities in Rhizospheric Soil of Green Pea

Abstract: To study the effect of incorporation of organic, inorganic and biofertilizers on rhizospheric microbial population and enzyme activities at various time intervals in pea crop, the experiment was laid in randomized blocked design in triplicate with plot size of 7 ×2.5 m 2 using Punjab-88 variety. Study was conducted during winter season of 2015-16 in field of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…(Buragohain et al, 2017) [2] . These results are in confirmity with the findings of Kaur et al (2017) [10] and Vajantha et al (2012) [21] .…”
Section: Alkaline Phosphatasesupporting
confidence: 93%
“…(Buragohain et al, 2017) [2] . These results are in confirmity with the findings of Kaur et al (2017) [10] and Vajantha et al (2012) [21] .…”
Section: Alkaline Phosphatasesupporting
confidence: 93%
“…Similar results were reported by Abd elgwad. (2019) in cowpea with higher dehydrogenase due to microbial inoculation and Kaur et al, (2017) in greenpea there was higher dehydrogenase, urease and alkaline phosphatase in soil due to addition of co-inoculation of bioinoculants. The lower enzymes activity in soil was observed in control with no bioinoculants seed inoculation might be due to restricted root growth and lesser exudates from roots which might have caused lower enzymes activity in soil.…”
Section: Effect Of Bioinoculants On Microbial Biomass Carbon Nitrogen...mentioning
confidence: 96%
“…In both acidic and charland soils, however, we found that IPNS or chemical fertilizer exerted on influence on PSB. This may be attributed to: firstly, the smaller amount of PSB population present in the organic amendments; and secondly, the inhibitory effect of inorganic phosphate applied via chemical fertilizer on the growth of PSB (Kaur et al, 2017).…”
Section: Effect Of Ipns On Microbial Populationmentioning
confidence: 99%